Hands off telecom give deregulation a chance. - Langley, M. (IEEE spectrum)
The US congress and the Federal Communications Commission (FCC) should stop micromanaging so the industry, in time, can shake out, wake up, and begin growing again. The US telecommunications industry has been in critical condition for more than a year; some claim that even its industry leaders are at death's door. Almost one-third of a million people in the industry have lost their jobs in one year, and dozens of leading firms have filed for bankruptcy protection. Is it time for government to step in? Absolutely not! The US congress and the US FCC should stop thinking they can facilitate competition. Industry should be allowed to take care of itself. Maintain a hands-off policy and the benefits of deregulation-competition in the local loop, lower prices, better services, increased demand, and more will materialize, and the industry will become healthy once again.